2008
DOI: 10.1590/s1676-26492008000200003
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic carbamazepine (CBZ) and valproic acid (VPA) monitoring in children using saliva as a biologic fluid

Abstract: Objective: The aim of the study was to analyze retrospectively carbamazepine (CBZ) and valproic acid (VPA) salivary data collected from epileptic children during a 3-year period. Methods: Saliva samples stimulated by citric acid were assayed by FPIA method. One hundred and three patients (aged 1-14 years) were in CBZ or VPA monotherapy or in CBZ-VPA combined therapy. Results: VPA salivary levels were linearly related with daily dose, but a non-linear relationship was found for CBZ, in patients under monotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
(11 reference statements)
0
3
0
1
Order By: Relevance
“…Our group has been working intensively with salivary concentrations of anticonvulsants [ 24 – 26 ]. For a number of drugs, mainly those which are lipophilic and nonionized at salivary pH range (i.e., phenytoin or carbamazepine), studies have demonstrated that salivary concentrations highly correlate with free drug concentration in plasma and therefore are more reflective of the concentration in the biophase [ 24 , 25 ]. If drug diffusion into saliva is only passive, the factors involved in drug excretion to this fluid are its lipophilicity and the degree of ionization.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has been working intensively with salivary concentrations of anticonvulsants [ 24 – 26 ]. For a number of drugs, mainly those which are lipophilic and nonionized at salivary pH range (i.e., phenytoin or carbamazepine), studies have demonstrated that salivary concentrations highly correlate with free drug concentration in plasma and therefore are more reflective of the concentration in the biophase [ 24 , 25 ]. If drug diffusion into saliva is only passive, the factors involved in drug excretion to this fluid are its lipophilicity and the degree of ionization.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of patients (27 children and 9 adults) with attention-deficit/hyperactivity disorder (ADHD) a significant correlation between concentrations of methylphenidate in serum and saliva was found (167). Some studies have tried to document the potential of measuring different psychoactive substances in OF, such as antipsychotics (168,169), antidepressants (170) and antiepileptic drugs (171).…”
Section: Oral Fluid 15mentioning
confidence: 99%
“…But, free drug monitoring is rather expensive for routine practice. Our research group has been working for several years using saliva as biological fluid [4][5][6]. Saliva is not only useful for being a simple and noninvasive collection method but also for the information it gives.…”
Section: Introductionmentioning
confidence: 99%